(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Due to the rising prevalence of polypharmacy in elderly patients, there has been a substantial increase in clinically relevant drug-drug interactions (DDIs) that can be a serious threat to patient safety, therapeutic efficacy and overall healthcare outcomes. Elderly individuals are extremely susceptible to the negative consequences of DDIs, including hospitalization, functional decline, and mortality, because they have age-related physiological changes and chronic comorbidities. Objective: In this study, specific and high-risk drug-drug interactions in polypharmacy regimens among elderly patients are systematically investigated, and their clinical implications are evaluated regarding adverse drug reactions (ADRs), hospitalization rate, treatment complexity. Methods: A robust mixed-methods approach was taken. (1) Systematic review of 60+ peer-reviewed articles and clinical guidelines from 2015–2024, (2) retrospective clinical analysis of electronic medical records of elderly patients in three tertiary hospitals, (3) 80 structured surveys and interviews with geriatricians, pharmacists and primary care providers. Variables of interest that were investigated include drug classes, levels of interaction severity, types of ADRs, and clinical outcomes related to ADRs. Results: Consequently, analysis of the high-risk DDIs involving anticoagulants such as warfarin, antidiabetics, antihypertensives, and CNS agents, for instance, contributed to a 45% increase in clinical adverse events of gastrointestinal bleeding, hypotensive episodes, as well as cognitive impairment. About 37% of hospitalized DDIs in elderly patients occurred. While alarming, 58% of surveyed clinicians confessed to limited access to up-to-date DDI screening tools and over 40% did not receive formal training in geriatric pharmacology. Conclusion: But this, the authors say, underlines how essential it is to increase pharmacovigilance and the personalization of drug prescribing for elderly people undergoing polypharmacy. Comprehensive Medication Reviews, clinician use of clinical decision support systems (CDSS) and geriatric-specific prescribing guidelines are critical for minimizing harm related to DDI. This vulnerable population cannot be protected without proactive clinician education and policy reforms. Future longitudinal studies will be necessary to evaluate the continued impact of future intervention strategies on DDI prevention and patient outcomes.